Comparative Study on Khar Mulching and Forest Litter Mulching: Soil Nutrient Dynamics in Ginger Cultivation - Aryal, Dipendra; Khanal, Babu Ram; Devkota, Pawan; Gupta, Kiran Kumar (International Journal of Applied Sciences and Biotechnology, 2019)
A study conducted to assess the fertility status under Khar(Pragmites karka) and forest litter mulching practices on ginger cultivation. Ginger field with mulching of Khar and ginger field with mulching of forest litter was identified as two strata to collect soil sample. Thirty soil samples collected from each mulching practices. Simple random sampling procedure was followed to collect soil sample within the strata. Soil fertility parameters such as soil pH, Soil organic carbon, Nitrogen, Phosphorus, Potassium were analyzed for different mulching system. Mulching material significantly effect on Soil pH, Soil organic carbon and soil nitrogen. Soil acidity was found lower with forest litter mulch (5.53) but it was found higher for Khar mulch (5.78). Soil organic carbon was found higher in ginger field with Khar mulch (2.31%) and found lower with forest litter mulch (1.97%). Soil nitrogen level was found higher in ginger field with Khar mulch (0.20%) and found lower with forest litter mulch (0.17%). Soil available phosphorus and Potassium were not found significantly different in both type of mulching system. The result obtained from the study indicates that ginger field with Khar mulch result soil with higher soil organic carbon and Nitrogen. Mulching decision can also be made after testing the soil of respective ginger growing field. Appropriate liming could be done so that it could reduce the soil acidity problems. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 335-340